Psychrotrophic bacteria and their negative effects on milk and dairy products quality - Šimun Zamberlin; Dubravka Samaržija; Tomislav Pogačić (Mljekarstvo)
The characteristics of bacterial populations in raw milk at the time of processing has a significant influence on shelf-life, organoleptic quality, spoilage and yields of raw milk, processed milk as well as on the other dairy products. Unfortunately, cold and extended storage of raw milk, as a common practice in dairy sector today, favour the growth of psychrotrophic bacteria. Therefore, their count in the refrigerated milk is more than the ideal limit of 10 % of the mesophilic count. Psychrotrophic bacteria are generally able to form extracellular or intracellular thermo-resistant enzymes (proteases, lipases, phospolipases) which can contribute to milk and dairy products spoilage. In addition, besides exhibiting spoilage features, some species belonging to the psychrotrops are considered as emerging pathogens that carry innate resistance to antibiotics or produce toxins. In sense of quality, psychrotrophic bacteria have become major problem for today’s dairy industry as leading cause in spoilage of cold-storage milk and dairy products. This review article focuses on the impact of psychrotrops on quality problems associated with raw milk as well as on th final dairy products. Means of controlling the dominant psychrotrophic species responsible for undesirable activities in milk and dairy products were also discussed.